A dádiva no ritual da Procissão do Fogaréu na Cidade de Goiás - Pinheiro, Ana (2004)
This dissertation is a bibliographic and empirical study which intends to aunch in the academic milieu not only the gift-giving analysis but its role in production and reproduction of social ties as well as its place and importance in the different forms of societies. Based on Mauss theory, gift-giving is in all societies, be modern, be traditional. This theory comprises of a genuine social system, with its own specificities and differences. The present study contains a discussion based on those authors who were inspired by Maussian literature. Mauss argues that the gift-giving is a paradigm which is peculiar to social sciences and he suggests that a societys formed by a primary social rule, that is, the process of gift-exchange for giving, receiving and rewarding. All of them create the cement bonds of social solidarity which are more important than the output of goods. In the light of Mauss theory, this research aims to link his ideas and Procissão do Fogaréu da Cidade de Goiás Cresset Procession in Goiás Town -. It presupposes that the procession is seen as an event which dramatizes the major gift-giving act in the Christian imaginary, that is, Jesus Christ donation to save the world. The procession is a dramatic representation whose ritual reports the bible text, and at same time, the local tradition which is experienced and defined by the people who live in Goiás Town.